Molecular characterisation of a cognate 70 kDa heat shock protein of the protozoan parasite Theileria parva - Daubenberger, C.A.; Heussler, V.; Gobright, E.I.; Wijngaard, P.L.J.; Clevers, H.C.; Wells, C.; Tsuji, N.; Musoke, A.J.; McKeever, Declan J. (Elsevier, 1997)
Theileria parva, a tick-transmitted protozoan parasite, infects cattle in eastern, central and southern Africa, leading to an acute, usually fatal lymphoproliferative disorder known as East Coast fever (1). It has been shown that the protective immune response against T. parva is mediated by class I MHC-restricted CD8+ cytotoxic T lymphocytes (CTL) recognising schizont transformed lymphoblasts (TpM) (2). Antigens expressed by TpM that constitute targets for CTL have yet to be identified. Therefore, a library was constructed from Poly(A) + RNA derived from a TpM cell line, D409/N2 (3). From this library, several colonies carrying parasite encoded genes were identified and are currently being characterised. Since heat shock proteins (hsp) of many infectious agents are known to constiute dominant antigens that may play an important role in the host-parasite relationship (4), we focused our attention on a newly cloned hsp gene, with the aim of elucidating its relevance to T. parva immunity.